Coccidioidomycosis outbreak among inmate wildland firefighters: California, 2017. Issue 4 (23rd January 2021) - Laws, Rebecca L.; Jain, Seema; Cooksey, Gail Sondermeyer; Mohle‐Boetani, Janet; McNary, Jennifer; Wilken, Jason; Harrison, Robert; Leistikow, Bruce; Vugia, Duc J.; Windham, Gayle C.; Materna, Barbara L.
Abstract: Background: In California, state prison inmates are employed to fight wildfires, which involves performing soil‐disrupting work. Wildfires have become more common, including areas where Coccidioides, the soil‐dwelling fungus that causes coccidioidomycosis, proliferates. However, work practices that place wildland firefighters at risk for coccidioidomycosis have not been investigated. Methods: On August 17, 2017, the California Department of Public Health was notified of a cluster of coccidioidomycosis cases among Wildfire A inmate wildland firefighters. We collected data through medical record abstraction from suspected case‐patients and mailed a survey assessing potential job task risk factors to Wildfire A inmate firefighters. We described respondent characteristics and conducted a retrospective case–control investigation to assess coccidioidomycosis risk factors. Results: Among 198 inmate firefighters who worked on Wildfire A, 112 (57%) completed the survey. Of 10 case‐patients (four clinical and six laboratory‐confirmed), two were hospitalized. In the case–control analysis of 71 inmate firefighters, frequently cutting fire lines with a McLeod tool (odds ratio [OR]: 5.5; 95% confidence interval [CI]: 1.1–37.2) and being in a dust cloud or storm (OR: 4.3; 95% CI: 1.1–17.4) were associated with illness. Two of 112 inmate firefighters reported receiving coccidioidomycosis training; none reported wearing respiratory protection on this wildfire. Conclusions: Wildland firefighters who use hand tools and work in dusty conditions where Coccidioides proliferates are at risk for coccidioidomycosis. Agencies that employ them should provide training about coccidioidomycosis and risk reduction, limit dust exposure, and implement respiratory protection programs that specify where respirator use is feasible and appropriate.